An effective approach to the fast, GPU-Based, Through-Wall imaging - Capozzoli, A.; Curcio, C.; D’Elia, G.; Iadarola, G.; Liseno, A.; Vinetti, P. (Видавництво Національного університету "Львівська політехніка", 2009)
We present an approach for the Through-Wall-Imaging based on a simple model of the scattering problem involving few unknowns, exploiting effectively the a priori information on the scenario and using a global optimization approach, relying on Legendre- Fenchel Transforms, tailored to fast, parallel implementations on Graphic Processing Units (GPUs). Experimental results are presented against X-band data collected in a realistic scenario made of a wall of Ytong concrete blocks and a metallic cylindrical scatterer.
Keywords: Through-Wall Imaging; GPU; Global Optimization; Legendre-Fenchel Transform; LLT